Mitochondria-targeted ratiometric fluorescent detection of hydrazine with a fast response time. (15th January 2018) - Ban, Yanan; Wang, Ruihui; Li, Yang; An, Zhen; Yu, Mingming; Fang, Chenjie; Wei, Liuhe; Li, Zhanxian
Abstract : A fluorescent hydrazine-probe was synthesized, which exhibited high sensitivity, excellent selectivity and anti-interference ability. Abstract : A ratiometric fluorescent probe1 was synthesized, which exhibited high sensitivity and excellent selectivity for hydrazine recognition. Probe1 can quantitatively detect hydrazine in the concentration range from 30 to 180 μM with a LOD of 2.1 μM. Furthermore, it displayed excellent selectivity, anti-interference over many nucleophilic species, biological species, metal ions and anions, and a fast response time (4 min). Due to its ability to target mitochondria, the response of hydrazine to this probe in a living cell was successfully tracked in a ratiometric manner via fluorescence imaging.